Aerosol clustering in an urban environment of Beijing during (2005–2017). (15th September 2019) - Shaheen, Kausar; Shah, Zarbad; Suo, HongLi; Liu, Min; Ma, Lin; Alam, Khan; Gul, Alia; Cui, Jin; Li, Chunyan; Wang, Ya; Khan, Shahid Ali; Khan, Sher Bahadar
Abstract: In depth and detailed study about various classes of aerosols over an urban city of Beijing has been carried out, with the help of cluster technique during the period from (2005–2017). Aerosol Robotic Network (AERONET), retrieved data for Aerosol Optical Depth (AOD), Angstrom Exponent (AE), Extinction Angstrom Exponent (EAE), Absorption Angstrom Exponent (AAE), Single Scattering Albedo (SSA), Real and Imaginary index of Refraction (RRI & IRI respectively), Asymmetry Parameter (ASY) has been utilized for discrimination of aerosols over the study site. Higher mean values of AOD and AE were found in winter and spring season as (0.86 ± 0.38, 0.85 ± 0.32) and (1.06 ± 0.36, 1.19 ± 0.21), while lower values (0.75 ± 0.33, 0.75 ± 0.33) and (0.97 ± 0.22, 0.85 ± 0.17) for summer and autumn season respectively, representing mixed anthropogenic aerosols over the site. Three main types of aerosol were reported in this study: Mixed Carbonaceous (MC), Biomass Residuals (BR), and coarse mode local and transported Dust Particles (DP). Various aerosol parameters and their inter-relationship were investigated in detail to analyze the dominant aerosol type and its seasonal variations. The EAE and AAE values ranged from (0.10–1.77 and 0.00–1.70 respectively), could mainly be attributed towards MC aerosols. Real and Imaginary parts of Index (RRI & IRI) were recorded in the range from (1.33–1.60 and 0–0.010) respectively. Similarly, the range for SSA and ASY was found as (0.79–0.99 and 0.43–0.78) respectively. Back-trajectories using Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model revealed transportation of air masses from Mongolian deserts, Gobi desert, and other neighboring regions (i.e. Russia and Kazakhstan). Highlights: Aerosols study of Beijing AERONET AOD Carbonaceous aerosols